Attitude of Preschool Children to Adult Labor - Ergash qizi, Asadova Rukhsara (European Journal of Life Safety and Stability (2660-9630), 2021)
The obligatory quality of a comprehensively developed person is great diligence. The work of a preschool educator has its own characteristics. Preparing a child for work is the formation of his psychological readiness. Psychological readiness is the level of development of an individual that is sufficient for the successful development of any type of production.